The Influence of Government Policies and the Berani Cerdas Program of Central Sulawesi Province on the Competence of Scholarship Recipients at Tadulako University - Fahmi Surya Abdi; Isbon Pageno; M. Nuralamsyah (International Journal of Management Science and Information Technology, 2026)
This study aims to examine the influence of government policies and the Central Sulawesi Smart Brave Scholarship Program on student competence at Tadulako University. A quantitative survey approach was employed involving 370 scholarship recipients from the 2025/2026 academic year. Data were collected through a Likert-scale questionnaire and analyzed using descriptive statistics and multiple linear regression. The findings indicate that the implementation of government policies was perceived at a moderate level (mean = 74.07), while the Smart Brave Program was categorized as fairly effective (mean = 37.39). Student competence was found to be in the good category (mean = 46.46). Regression analysis revealed that government policies and the Smart Brave Program have a significant positive effect on student competence (p < 0.05). Furthermore, the coefficient of determination (R² = 0.576) shows that 57.6% of the variation in student competence can be explained by these two factors. These findings suggest that effective policy implementation and scholarship support play an important role in enhancing students’ competencies and academic development in higher education.